Angiotensin IV and the human esophageal mucosa: An exploratory study in healthy subjects and gastroesophageal reflux disease patients. (September 2015) - Björkman, Eleonora; Edebo, Anders; Fändriks, Lars; Casselbrant, Anna
Introduction: The human esophageal mucosa expresses various components of the renin-angiotensin system (RAS), e.g. the main effector peptide angiotensin II (AngII). The aim of this study was to investigate the esophageal presence of angiotensin III (AngIII) and angiotensin IV (AngIV) forming enzymes and the AngIV receptor (AT4R). The aim was also to study the actions of AngIV and to look for aberrations in patients with gastroesophageal reflux disease (GERD). Materials and methods: Esophageal biopsies were collected from healthy volunteers ( n : 19) and individuals with erosive reflux disease ( n : 14). Gene transcripts and protein expression of aminopeptidase A, -B and -M, and the AT4R were investigated by reverse transcriptase polymerase chain reaction (rt-PCR), western blot (WB) and immunohistochemistry (IHC). The functional impact of AngIV was examined in an Ussing chamber. Results: Aminopeptidase A, -B and -M and the AT4R were expressed in the esophageal epithelium. The AT4R was less prominent in certain areas in the mucosa of reflux patients. AngIV influenced the esophageal epithelial ion transport. The impact was lower in patients with GERD. Conclusion: The AT4R and formation enzymes of AngIII and AngIV are present in the human esophageal epithelium. Moreover, the present results suggest that AngIV exert regulatory impact on the epithelium and that RAS is involved in mucosal aberrations associated with GERD.